ChemInform Abstract: Reflections on the Chemistry of the Fischer—Tropsch Synthesis. Issue 6 (20th February 2013) - James, Olusola O.; Chowdhury, Biswajit; Mesubi, M. Adediran; Maity, Sudip
Abstract Review: 166 refs.